Analysis of the quality of test instrument and students’ accounting learning competencies at vocational school - Nur Ichsanuddin Achmad Kurniawan; Sudji Munadi (Graduate School, Universitas Negeri Yogyakarta, 2019)
The study is aimed at describing: (1) characteristics of the items of the national examination try-out test of the accounting subject matter in the 2015/2016 academic year on classical test theory and modern test theory; and (2) classification of students’ masteries in the learning of accounting. The study is explorative research. Analyses are conducted using the classical and modern test theories for item characteristics and descriptive quantitative for students’ masteries in accounting using the test set for the national examination try-out in the 2015/2016 academic year. A total of 414 students do the Package A test. Results show that (1) based on the classical test analyses, a number of 11 items (27.5%) belong to the “easy” category, 22 items (55%) “medium” category, and 7 items (17.5%) “difficult” category allowing a total of 19 (47.5%) to be categorized as good items; meanwhile, on the modern-theory analyses, a total of 34 items (85%) belong to the “good” category. (2) Around 38% of the students have competencies of the medium and low categories. Most students have difficulty in answering questions of the higher-order thinking levels.